Unlocking Potential, Sustaining Gains; Enhancing Women Farmers' Access to and Use of Climate Smart Innovations through the Private Sector; Insights from AICCRA Ghana - Obeng Adomaa, Faustina; Tepa Yotto, Ghislain (2025)
This InfoNote presents findings from AICCRA Ghana work with private sector businesses in scaling access to CSA and CIS innovations among women farmers through mainstreaming GSI considerations in inclusive business models as well as implementing customized programmes to target the unique needs of women